Disoriented disciplines : China, Latin America, and the shape of world literature - Hubert, Rosario (Evanston, Illinois : Northwestern University Press, 2024)
"This is a study of the archival formations, theoretical debates, and geopolitical frameworks that constructed an idea of China in Latin America from the nineteenth century to the present"--
Trade, tourism, and traffic : the labor routes of modernismo -- Sinology on the edge : Borges's fictional epistemology of China -- The twisted networks of cultural diplomacy : global Maoism in print -- The surface of the ideograph : visual poetry and the Chinese script -- Moving memories : the affective archive of the Cultural Revolution -- Afterword : "Imposture" -- Appendix : Translations into Spanish of Chinese literature published in Buenos Aires, 1942-81
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Latin American literature -- Chinese influences; Latin American literature -- History and criticism; Chinese literature -- Influence; Orientalism -- Latin America; Modernism (Literature) -- Latin America; China -- In literature; Latin America -- Intellectual life; Littérature latino-américaine -- Influence chinoise; Littérature latino-américaine -- Histoire et critique; Littérature chinoise -- Influence; Orientalisme -- Amérique latine; Modernisme (Littérature) -- Amérique latine; Amérique latine -- Vie intellectuelle; Chinese literature -- Influence; Intellectual life; Latin American literature; Literature; Modernism (Literature); Orientalism; China; Latin America; LITERARY CRITICISM / General; Criticism, interpretation, etc